Changing beliefs or changing behavior? Understanding the belief‐to‐behavior process and intervening to curb the impact of misinformation - Lee, Hogeun; Albarracín, Dolores (Journal of Consumer Psychology, 2026)
Abstract A common assumption among scientists, journalists, and policymakers is that combating misinformation reliably changes behavior. However, the empirical evidence reveals that the belief–behavior association is often modest, variable, and context‐dependent, raising critical questions about when and how to pursue belief versus behavior change. In this paper, we discuss the mechanisms by which beliefs influence behavior and the conditions under which addressing beliefs can change behavior. Specifically, we review the belief‐to‐behavior inference model, which proposes that beliefs influence behavior when (a) the belief is linked to a behavioral goal, (b) the inferential path from belief to behavior is relatively short, and (c) the belief–behavior association is preserved in memory. Our framework aligns intervention decisions with the cognitive architecture of belief–behavior correspondence and the intervention's goals, whether maximizing belief accuracy or behavioral impact. We also reviewed individual and social‐structural interventions that are best suited for changing beliefs versus behavior, conceptually integrating interdisciplinary work on behavior change with the psychology of belief change.